Español - Mejía Martínez, Francisco (2022)
Maritime interests are a fundamental pillar for the development of States, and for that, a Naval Power is required to protect them. The Maritime Power of a State is made up of both maritime interests and naval power. A naval power must be able to be used diplomatically, as in its primary tasks of National Defense, and for this, warships have their attributes; that is, political flexibility, operational flexibility, logistical flexibility, and arrival-ready condition. The warship is an instrument of the State to be used in crisis management, with the purpose of achieving a political objective without passing the threshold of critical aggressiveness, because if this occurs, it would be in what is called war with another State. If the political objective that comes into play is vital for any of the Parties, then the warship will be used to carry out naval operations that seek to defend national interests. The Naval Force of El Salvador has shown the important role it plays; firstly, in its constitutional mission of National Defense; and second, in cooperation with the international community, specifically, in the fight against drug trafficking. In this type of operations, it interoperates with large navies such as the US and medium-sized ones such as Mexico and Canada.